A study of screen printing of stretchable circuits on polyurethane substrates - Zhong, Zhao Wei (2021)
The interest in flexible stretchable printed electronics has increased because of the wide applications, especially for wearables devices. The conventional manufacturing processes were time consuming and expensive, which led to developing of stretchable interconnects using screen printing. In this research, meander patterns of varying meander angles were designed and screen-printed on thermoplastic polyurethane substrates. Silver inks and carbon inks were used to print the circuits, which were subjected to tensile tests while their changes in resistance were measured. The electrical characteristics were utilised to determine the elastic limits of the circuits and the conditions for cyclic tests of up to 10,000 cycles. It was found that the maximum strain at break of the silver ink was 47%. Carbon ink had a higher initial resistance value and the maximum strain at break was 125%. The best stretchability was obtained at the 0° meander angle, a curing time of 30 min and curing temperature of 130 °C with oven cooling.